A system and a method to determine moisture content of agricultural raw material - Abbas, Zulkifly; Zainuddin, Mohamad Faiz; Ansaruddin, Farizah (2012)
The present invention discloses a system (100) for determining an estimated moisture content of an agricultural raw material comprising a network analyzer (103) for generating wave signals of a predetermined frequency to measure a reflection coefficient value of air and a reflection coefficient value of the material; a coaxial cable (102) formed by an inner conductor (104) surrounded by multiple tubular layers, having a portion of the inner conductor (104) extending out from the tubular layers at a first end of the cable (102) and the cable (102) connecting to the network analyzer (103) at a second end of the cable (102); a cable connector (106) having a first opening end for the cable (102) to be connected thereto by inserting the first end of the cable (102) through the connector (106) and a second opening end for the extended inner conductor (104) of the cable (102) to be projected out of the connector (106); and a metal plate (105) being perpendicularly disposed in between the second opening end of the connector (106) and the extended inner conductor (104), with the extended inner conductor (104) protruding from the center of the plate (105); wherein the inner conductor (104), connector (106) and metal plate (105) forms a sensor probe (101) for contacting the material at the predetermined frequency to determine the estimated moisture content through calculations based upon a normalized reflection coefficient value which could be the magnitude of reflection coefficient and/or phase shift of reflection coefficient acquired from the measured reflection coefficient values of the air and material and an actual moisture content value of the material that is obtained through calculations in accordance with a drying method. Such system is used to determine the moisture content of Dioscorea hispida. The present invention could also include a tubular insulator (107) surrounding the extended inner conductor (104) for determining the moisture content of Hevea rubber latex.